Manifestaciones orales frecuentes en personas con Síndrome de Down. Una revisión de la literatura - Marín Sáez, Isidora; Maldonado Tisi, Juan José; Bancalari Selman, Carla (Journal of Oral Research, 2021)
Down syndrome (DS) is one of the most common genetic disorders in the world, with an estimated incidence of 1 per 600-1,000 live births. Its origin is in 95% of the cases due to the presence of an additional copy of chromosome 21, followed by translocation (2%–4%) and isochromosomal mosaicism (1–2%).